Association between discordant immunological response to highly active anti-retroviral therapy, regulatory T cell percentage, immune cell activation and very low-level viraemia in HIV-infected patients. (24th April 2014) - Saison, J; Ferry, T; Demaret, J; Maucort Boulch, D; Venet, F; Perpoint, T; Ader, F; Icard, V; Chidiac, C; Monneret, G
Summary: The mechanisms sustaining the absence of complete immune recovery in HIV-infected patients upon long-term effective highly active anti-retroviral therapy (HAART) remain elusive. Immune activation, regulatory T cells (Tregs ) or very low-level viraemia (VLLV) have been alternatively suspected, but rarely investigated simultaneously. We performed a cross-sectional study in HIV-infected aviraemic subjects (mean duration of HAART: 12 years) to concomitantly assess parameters associated independently with inadequate immunological response. Patients were classified as complete immunological responders (cIR, n  = 48) and inadequate immunological responders (iIR, n  = 39), depending on the CD4 + T cell count (> or < 500/mm 3 ). Clinical and virological data (including very low-level viraemia) were collected. In parallel, immunophenotyping of CD4 + lymphocytes, including Treg subsets, and CD8 + T cells was performed. Percentages of activated CD4 + T cells, Tregs, effector Tregs and terminal effector Tregs were found to be significantly elevated in iIR. Neither the percentage of activated CD8 + T cells nor VLLV were found to be associated with iIR. In the multivariate analysis, nadir of CD4 + T cell count and percentage of Tregs were the only two parameters associated independently with iIR [odds ratio (OR) = 2·339, P  = 0·001, and OR = 0·803, P  = 0·041]. We present here the largest study investigating simultaneously the immune response to long-term HAART, activation of CD4 + and CD8 + T cells, Treg percentages and very low-level viraemia. Causative interactions between Tregs and CD4 + T cells should now be explored prospectively in a large patients cohort.